2010
DOI: 10.1590/s0366-69132010000200015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of the Ca2MnReO6 double perovskite

Abstract: The Ca2Mn1Re1O6 double perovskite has been prepared in polycrystalline form by using the encapsulated quartz tube method. The partial oxygen pressure inside the quartz tube revealed this to be a crucial synthesis parameter for the production of a single structural phase sample. This parameter was controlled using the ratio between ReO2 and ReO3 content and the filling factor parameter (ratio between mass and total inner volume of the quartz tube). The morphology and chemical composition was investigated by sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…The tolerance factor is calculated and is found to be between (1.008 -1.020) as shown in Table 1. This is confirmed the (Fm-3m) cubic structure according to the criteria adopted by Correa et al and Popov et al [12] [13]. Figure 4(a) and Figure 4(b) show the relation between the tolerance factor and volume of unit cell respectively with ratio of replacement.…”
Section: Xrd Refined Resultssupporting
confidence: 79%
“…The tolerance factor is calculated and is found to be between (1.008 -1.020) as shown in Table 1. This is confirmed the (Fm-3m) cubic structure according to the criteria adopted by Correa et al and Popov et al [12] [13]. Figure 4(a) and Figure 4(b) show the relation between the tolerance factor and volume of unit cell respectively with ratio of replacement.…”
Section: Xrd Refined Resultssupporting
confidence: 79%
“…A major consequence of the distortion is that the Mn-O-Re angle is considerably lower than 180º. The relevant bond-lengths and angles are shown in Table II. No secondary phases or impurities were observed in the diffraction pattern of Ca 2 MnReO 6 and the structural parameters are the same to the ones reported by Corrêa et al [16] and similar to the ones reported by Kato et al [22]. Residual traces of CeO 2 were found in the Ca 1.8 Ce 0.2 MnReO 6 , which was remarked as second set of tick marks in the diffraction pattern (Fig.1b).…”
Section: Crystal Structuresupporting
confidence: 88%
“…However, we used the notion of first moment (E m ) of the white-line proposed by Alp et al [26] to estimate the chemical shift. This notion also was used by Popov et al [6] and Corrêa et al [16]. The values found were ~ +5.7 and ~ +5.8 to Ca 2 MnReO 6 and Ca 1.921 Ce 0.079 MnReO 6 samples, respectively.…”
Section: /N)the Errors Represent the Standard Deviation (Statisticalsupporting
confidence: 51%
See 1 more Smart Citation
“…Hence Cu-substitution into CMFR to give CMCFR promotes metallicity and leads to an increase in both ordering temperatures and saturated magnetisation. Fe 3+ and Re 5+ are present at the B-sites in the above materials, but the double perovskites Ca2MnReO6 21 and Mn2MnReO6 12 are found to have Mn 2+ and Re 6+ , so the composition CaMnMnReO6 (CMMR) has been investigated to discover if the same charge configuration can be stabilized in the P42/n double double perovskite arrangement. This phase was successfully synthesized with a small 3.6(2) % impurity of MnO and structure refinement against PND data reveals a high degree of cation order with 4.0(1)% of Mn/Re antisite disorder, and also 5.4(2)% Mn occupancy of the Ca site.…”
mentioning
confidence: 99%